It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences

La grand-maternité chez les Inuits Portrait d’une réalité méconnue - Sigouin, Catherine; Charpentier, Michèle; Quéniart, Anne (Nouvelles pratiques sociales, 2011)
Cet article explore la grand-maternité telle qu’elle est construite et vécue chez les Inuits du Nunavik, à partir d’une recension de la littérature ainsi que des résultats préliminaires d’une recherche qualitative visant à connaître le point de vue des grands-mères inuites sur leur place et leurs rôles au sein de la famille. L’étude met notamment en lumière la place centrale et indispensable des grands-mères dans les soins et l’éducation des petits-enfants. Elle soulève également certains questionnements quant à la pertinence des programmes psychosociaux actuellement en place. Ces observations tendent en faveur d’une reconnaissance du rôle essentiel des grands-mères inuites à travers la mise en place de programmes et de services mieux adaptés à cette clientèle.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; féminisme autochtone; féminisme décolonial; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; travail social; trs1205